PENGARUH KEPEMIMPINAN TERHADAP DISIPLIN KERJA KARYAWAN PADA PT. BANK SYARIAH MANDIRI - JELI NATA LIYAS (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2017)
The theme of the article is "economy based on the principles of Islam". The purpose of this study was to determine the influence of leadership on employee discipline at PT. Bank Syariah Mandiri Branch Duri.population in this research is all employees at PT. Bank Syariah Mandiri Branch Duri which amounted to 41 people, So the sample taken in this study is all employees of PT. Bank Syariah Mandiri Duri Branch Office amounting to 40 people, this is because the leader is the object studied in this study, therefore the leadership is not included in this study. Data analysis used in this research is descriptive and quantitative analysis method. In this research used simple linear regression analysis model. Y = 16,679 + 0,591X, hence can be seen constant 16,679. Means when the leadership is considered constant, the discipline of work is 16.679, while the leadership (X) of the work discipline is positive as evidenced by the result b = 0,591 which means that any increase in leadership one unit will be able to raise the discipline of employees at PT. Bank Syariah Mandiri Branch Duri of 0,591 units. Can be obtained r-square value (coefficient of determination) of 0.384. This shows that leadership contributes to the influence of employee work discipline at PT. Bank Syariah Mandiri Branch Duri amounted to 38.4% while the rest (100% -38.4%) = 61.6% influenced by other variables outside the variable in this study.